2009
DOI: 10.1002/art.25053
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sustained improvement in bone and cartilage turnover markers with the anti–interleukin‐6 receptor inhibitor tocilizumab plus methotrexate in rheumatoid arthritis patients with an inadequate response to methotrexate: Results from a substudy of the multicenter double‐blind, placebo‐controlled trial of tocilizumab in inadequate responders to methotrexate alone

Abstract: Objective. To investigate the effects of tocilizumab (TCZ) added to a stable dosage of methotrexate (MTX) on biochemical markers of bone and cartilage metabolism in patients inResults. TCZ induced marked dose-dependent reductions in PIIANP, HELIX-II, and MMP-3 levels at week 4 that were maintained until week 24, an effect associated with increased levels of bone formation markers that were significant as compared with placebo only for PINP and only at 4 weeks (P < 0.01 for both TCZ doses). TCZ induced signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
95
1
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(120 citation statements)
references
References 47 publications
(75 reference statements)
8
95
1
13
Order By: Relevance
“…Our literature search found 2 RCTs that examined the effects of tocilizumab, an IL-6 receptor inhibitor, on bone turnover markers in RA (29,30). Both studies found that tocilizumab administered at 4 mg/kg and 8 mg/kg for 24 weeks was associated with significant reduction in bone resorption markers, C-terminal crosslinking telopeptide of type I collagen generated by matrix metalloproteinases, and C-terminal crosslinking telopeptide of type I collagen compared with placebo.…”
mentioning
confidence: 99%
“…Our literature search found 2 RCTs that examined the effects of tocilizumab, an IL-6 receptor inhibitor, on bone turnover markers in RA (29,30). Both studies found that tocilizumab administered at 4 mg/kg and 8 mg/kg for 24 weeks was associated with significant reduction in bone resorption markers, C-terminal crosslinking telopeptide of type I collagen generated by matrix metalloproteinases, and C-terminal crosslinking telopeptide of type I collagen compared with placebo.…”
mentioning
confidence: 99%
“…These findings suggest a slight but significant positive effect of a mixture of methotrexate, placebo, and disease progression on the bone biomarker changes over a long‐term period. In a clinical trial of patients with RA receiving tocilizumab or placebo with methotrexate, median P1NP, and OC, CFB in the placebo group seemed to increase at 24 weeks, although it was reported as nonsignificant 27. In another study, urinary excretion levels of N‐telopeptide of type I collagen (bone resorption marker) significantly decreased in patients with RA treated with methotrexate 28…”
Section: Discussionmentioning
confidence: 99%
“…Также лече-ние ТЦЗ сопровождается падением концентрации маркеров костной деструкции CTXI и карбокситерминального тело-пептида коллагена I типа (ICTP). Следует отметить, что снижение уровня ICTP, HELIXII, MMП3 более выражено у ответивших на терапию ТЦЗ, чем в группе больных с отсут-ствием такого ответа [54].…”
Section: тоцилизумабunclassified